Proximity induced signatures of elusive Bose metal phase in topological insulator- superconductor junction - Reena Yadav; Mandeep Kaur; M. P. Saravanan; Sudhir Husale (Scientific Reports)
Abstract The quantum metal state (QMS) occurring between the superconductor and insulator transition is often considered a Bose metal phase (BMP) whose understanding remains elusive and has been under debate even though studied for decades. To observe the BMP one needs to disrupt the phase coherence and search it into 2D amorphous, disorder, defective or nanoengineered superconducting materials. Superconductor -Topological insulator (SC-TI) junctions host the exotic nature of quasiparticles and are expected to show 2D superconductivity. Here, for the first time, we harness exotic SC-TI junctions investigating signatures of BMP and report proximity induced low temperature transport through superconductor-bismuth telluride (SC-Bi2Te3) nanosheet junctions. Transport data reveals superconducting effects in the nanosheets and the existence of the resistive metallic state with reentrant nature. We analysed the data to show the appearance of different quantum states. For longer junction lengths (1.1 & 0.78 μm), temperature-dependent resistive humps having similar peak heights and widths in the magnetoresistance (MR) curves were observed which were suppressed for smaller junction length (310 nm). The hump signatures in MR curves and scaling analysis of the data indicate the appearance of BMP. Our results suggest that SC-TI junctions exhibiting partial superconductivity are necessary to witness a peculiar metallic state resembling a BMP.